Pencegahan Perceraian Dini di Kabupaten Indramayu Perspektif Hukum Islam dan Hukum Positif - Miftahudin Azmi (Universitas Wahid Hasyim Semarang, 2023)
Divorce in the Indramayu Regency is an intriguing phenomenon to investigate because the bulk of divorce cases are carried out by young couples (under 25 years old). Arahan District is one of the areas in Indramayu with a relatively high divorce rate. In 2021, the divorce rate in Arahan District was 52 persen of the total number of marriages, implying that more than half of marriages ended in divorce. The goal of this research is to examine the causes of early divorce as well as the measures to overcome them. This article falls under the empirical category and takes a qualitative approach. The key references are obtained through interviews and assessed using a positive legal perspective. The findings revealed that a lack of public interpretation of the purpose of marriage, a lack of knowledge of the sakinah family, emotional attitudes in problem-solving, excessive jealousy, a lack of responsibility, domestic violence, a lack of parental control, and economic factors all contributed to the high number of divorces among young couples. Among the several measures to combat child marriage and divorce are raising the marriage age for women, establishing sakinah families for prospective brides, and offering premarital education assistance.Keywords: Prevention; Divorce of young age; Islamic Law; Positive LawAbstrakFenomena perceraian di Kabupaten Indramayu menjadi kajian diskusi yang cukup menarik, sebab kasus perceraian itu mayoritas dilakukan oleh pasangan muda (dibawah 25 tahun). Salah satu daerah di Indramayu yang menyumbang angka perceraian cukup tinggi adalah Kecamatan Arahan. Angka perceraian di Kecamatan Arahan pada tahun 2021 berjumlah 52 persen dari angka perkawinan pada tahun tersebut, artinya lebih dari separuh perkawinan berujung pada perceraian. Tujuan penelitian ini adalah menganalisa penyebab terjadinya perceraian dini dan upaya menanggulanginya. Artikel ini termasuk kategori empiris dengan pendekatan kualitatif. Adapun rujukan primer bersumber dari wawancara dan dianalisa dengan pendekatan hukum positif. Hasil penelitian menunjukkan bahwa banyaknya perceraian pasangan usia muda disebabkan minimnya interpretasi masyarakat tentang makna perkawinan, rendahnya pemahaman terkait keluarga sakinah, sikap emosi dalam menyelesaikan masalah, kecemburuan yang berlebihan, minimnya tanggung jawab, hingga Kekerasan Dalam Rumah Tangga (KDRT), minimnya kontrol dari orang tua, serta aspek ekonomi. Berbagai upaya menanggulangi pernikahan dan perceraian anak antara lain ialah menaikkan batas usia perkawinan bagi perempuan, pembekalan keluarga sakinah bagi calon pengantin dan bimbingan edukasi pra nikah.Kata kunci: Pencegahan; Perceraian dini; Hukum Islam; Hukum Positif